Dramaturgia na dança-teatro de Pina Bausch - Juliana Carvalho Franco da Silveira (2009)
This dissertation attempts to find the strategies of composition used by Pina Bausch for the dramaturgical construction of the pieces of the Tanztheater Wuppertal, from 1973 to 2009. In the present research, to reflect about dramaturgy meant to observe the creation of the pieces in all its production context, which includes its aesthetic and thematic choices, and the proceedings utilized for the creation process and for the training of the dancers. For that, a bibliographic revision was done about the historical and the artistic context of the dance theater and the trajectory of Pina Bausch, about the concept of dramaturgy in theater and in dance, as well as the analysis of interviews, videos, statements, critics and reports about the work of the German director and choreographer. It was also realized a field research in the Tanztheater Wuppertal in February of 2008 and in April and May of 2009. Finally, this work searched out to establish parameters for the understanding of the dramaturgical composition of the work of Pina Bausch. Two different phases were identified in the creation process of the pieces: before and after the questions method. Centering in the second phase – that is the longest and goes from 1978 to 2009 – among the composition strategies found, it was detached the “question method”, the collage structure, the use of costumes that explicit social functions and of stage settings with organic material and quotidian objects, the dramaturgy that develops itself during the process of creation and has as its base the director’s look. The work of the German director developed in what Norbert Servos calls “theater of experience”, because its point of departure for the creation of the pieces is the subjective experience of the dancers. Observing the composition strategies, it is possible to say that Pina Bausch’s dance theater is a form of art that has the capacity to absorb and reflect contemporary life, expanding the expressive possibilities of dance and theater and feeding the search for new forms of expression for both genres.